Development of the composition and technology of extemporaneous suppositories with сlindamycin and sea buckthorn oil - Chushenko, V; Yarnykh, T; Osolodchenko, T; Yuryeva, G; Herasymova, I (Annals of Mechnikov’s Institute, 2019)
Introduction. Antibacterial therapy certainly plays an important role in the treatment of these pathologies, although in most cases it causes allergic states, antibiotic resistance of various types of microorganism strains, and also a disfunction of normal vaginal biocoenosis. Anti-protozoal, antibacterial and antifungal agents are preferred, namely, ternidazole, metronidazole, fluconazole, clindamycin, miconazole, clotrimazole, nystatin, isoconazole etc. among the synthetic drugs used in gynecological practice. Prospective plant medicines for solving this problem are essential oils (tea tree, sea buckthorn, wormwood, chamomile), which provide inhibition of the development of pathogenic anaerobes. The aim of the work was to substantiate the composition and development of technology of combined vaginal suppositories (pessaries) with clindamycin phosphate and sea buckthorn oil for the treatment of infectious-inflammatory gynecological diseases. Materials and methods. Model samples of suppositories were prepared with 0.100 g of clindamycin phosphate and 0.500 g of sea buckthorn oil. Disperse system of suppositories with clindamycin and sea buckthorn oil is an emulsion of 1st type, therefore it is possible to use as emulsifiers the following substances: polysorbate-80, emulsion wax or alkaline soaps. Model samples of suppositories with clindamycin phosphate and sea buckthorn oil were checked by pharmaco-technological parameters (description, homogeneity, disintegration time, pH). The study of antibacterial properties of suppository model samples with clindamycin and sea buckthorn oil was carried out. Results and discussion. Samples of suppositories with polysorbate-80 become homogeneous and meet the requirements of the SPhU 2.0. The results of the conducted researches of pharmaco-technological parameters shown that model samples of suppositories with clindamycin phosphate and sea buckthorn oil meet the requirements of the SPhU 2.0 for the following parameters: description, homogeneity, disintegration time, pH. Conclusions. The composition and technology of suppositories with clindamycin phosphate and sea buckthorn oil for pharmacy preparation was developed. A technological instruction for the pharmacy preparation of suppositories has been developed and tested in the conditions of pharmacy.